DIVERSITY OF SUBTERRANEAN TERMITES (BLATTODEA: TERMITOIDEA) ON VARIOUS TYPES HABITAT AROUND IPB UNIVERSITY CAMPUS, BOGOR, INDONESIA - Mubin, Nadzirum; Sakti Harahap, Idham; ., Giyanto (Universitas Lampung, 2019)
Termites are social insects that play an important role in ecosystem. Habitat is a crucial factors determining diversity of termites. IPB University campus has quite diverse habitat types. In this research, we study the diversity and abundance of termite species around IPB University campus. Two methods used for data collection, i.e. baiting system with pine wood and transect survey within 10 x 10 m area. Six species of termites found belongs to two families, Termitidae (Macrotermes gilvus, Odontotermes javanicus, Microtermes insperatus, and Capritermes mohri) and Rhinotermitidae (Schedorhinotermes javanicus and Coptotermes curvignathus). The most diverse with the high abundance of these termites are found in theÃ‚Â rubber trees area, Faculty of Fisheries (FPI) and the forest behind the main administration building, Rectorate (REK) because this area provides an abundant source of cellulose as a food source for termites. While the building areas tend to have a lower diversity and abundance index because food sources for termites are not always available due to human activities. Non-metric multidimensional scaling analysis shows that the termites species composition is different between study area.